IMPLEMENTASI GERAKAN BANTUL BERSAMA DALAM KURIKULUM MERDEKA UNTUK MENUJU SEKOLAH PEDULI DAN BERBUDAYA LINGKUNGAN - rahayu, sri (Jurnal Riset Daerah, 2022)
Efforts to protect, preserve, and manage the environment are not only the responsibility and obligation of the government, but also require the participation and active role of all components of society, both community groups, non-governmental organizations , the business world, as well as educational institutions (schools) and universities. In the implementation of the Independent Curriculum in a school, it can include environmental materials so that the implementation of the Independent Curriculum can be a solution to solving the waste problem that is being discussed in Bantul Regency as well as being able to help schools move towards a caring and environmentally cultured school that is directed towards Adiwiyata schools. The purpose of this study is to describe the implementation of the Joint Bantul Movement which can be carried out as an application of the Independent Learning Curriculum in a school to go to a school that cares and has an environmental culture. The research method is descriptive qualitative with the data analysis technique used is descriptive narrative analysis. The data were obtained from the results of observations, interviews and documentation to then be written in the form of a description and simplified according to the research focus. The implementation of the Joint Bantul Movement that can be carried out as the application of the Independent Learning Curriculum in a school includes: (1) the application of environmentally friendly policies; (2) implementation of the environment-based Independent Curriculum project; (3) establish participatory-based partnerships with the government, universities, other schools and the mass media; (4) conducting environmental-based study activities. Various experiences gained in implementing the Independent Curriculum provide opportunities for students and schools to be able to synergize and collaborate with various stakeholders (Government, Universities and the community) in a massive, intensive and sustainable manner to jointly support the Bantul Bersama Movement (Bantul Clean Garbage in 2025).